Effects of weight bearing and non-weight bearing sports on bone quality in male collegiate athletes - Freda, D.; Skoe, T.; Cave, C.; Wehrli, M.; Fox, B.; Alumbaugh, B.; Reeder, M.; Heumann, K. (Journal of Science and Cycling, 2017)
Introduction